Policzalne piękno? Matematyczno-fizyczne aspekty estetyki językowej = Countable beauty? The mathematic and physic aspects of the language aesthetics - Rutkowska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article accentuates the mathematic and physic aspects of the language aesthetics. That is why the language is treated, first and foremost, as a physical phenomena - measurable because of its acoustic and graphic representation. The clue of this work is the presentation of the conexions between mathematic and communication (the structure of text or speech).
Keywords: estetyka językowa; komunikacja językowa; akustyka; cyfryzacja; Libera, Antoni (1949- ); linguistic aesthetics; linguistic communication; acoustics; digitalization